Rights and obligations of the wife: concepts in the doctrine of family law and features of implementation in legal practice - Sydorenko, Denys (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The scientific article carries out a scientific study of the theoretical approaches defined in the family law doctrine for understanding the essence of the family rights of spouses and analyzes their practical application in legal practice. The article states that in the family law doctrine, the rights and obligations of spouses are defined as the subjective rights of the spouse or one of them, as a measure of possible or permitted behavior of the spouse, as corresponding powers that can potentially be exercised by him, based on and in accordance with the acts of family legislation, the family contract, the discretion of the spouses themselves, provided that this does not violate the rights and interests of other persons, as the type and measure of the necessary behavior that the spouse as a participant in family relations is obliged to perform. Personal non-property and property rights and obligations of the spouses are carried out with the joint consent of both spouses, which is usually oral in form (the written consent of the spouses is required only for concluding contracts regarding real estate, other valuable property, other contracts that require notarization or state registration, as well as in the case of settling the issue of terms, amount and terms of alimony payments to the other spouse, such consent is in writing, including in the form of a spousal maintenance agreement to the other spouse in the interests of the family (except for cases when the provision of oral or written consent of the other spouse is necessary for the exercise of marital rights or the performance of marital duties. In the event that the spouses reach an agreement regarding the exercise of their personal non-property and property rights and obligations relationships, this order will have priority compared to the order defined by family legislation; at the same time, it is possible to settle only the property rights and obligations of the spouses in a contractual manner. In the event of failure to reach a joint agreement on the exercise of family rights and the performance of family duties by the spouses or one of them, such an order shall be established by court order.